An Eco‐Friendly and Efficient Approach for the Synthesis of Tetrazoles via Fe3O4/HT‐GLYMO‐TA as a New Recoverable Heterogeneous Nanostructured Catalyst. Issue 21 (5th June 2020) - Ghasemzadeh, Maryam Sadat; Akhlaghinia, Batool
Abstract: Tannic acid immobilized on functionalized magnetic hydrotalcite (Fe3 O4 /HT‐GLYMO‐TA) was synthesized as a durable, environmentally‐friendly and magnetic nanostructured catalyst for the synthesis of 5‐ and 1‐substituted‐1 H ‐tetrazoles. The nanocatalyst was characterized by several methods, Fourier transform infrared (FT‐IR), X‐ray diffraction (XRD) analysis, transmission electron microscopy (TEM), field emission scanning electron microscopy (FE‐SEM), energy‐dispersive X‐ray spectroscopy (EDS), EDS‐map, thermogravimetric analysis (TGA), vibrating sample magnetometry (VSM) and CHNS analysis. The results displayed that the superparamagnetic catalyst with a mean particle size of approximately 23–27 nm has a plate‐like shape. The catalytic activity of this new nanostructured catalyst resulted in the preparation of tetrazoles with high yields. Additionally, this novel procedure offers a plethora of benefits including short reaction times, the simplicity of operation, the ease of purification procedure and the reusability of nanocatalyst for at least eight cycles. Abstract : In this research, tannic acid immobilized on functionalized magnetic hydrotalcite (Fe3 O4 /HT‐GLYMO‐TA (IV )) was prepared as a recyclable and efficient nanostructured catalyst for the syntheses of 5‐substituted‐1 H‐ tetrazoles and 1‐substituted‐1 H ‐1, 2, 3, 4‐tetrazoles in green media. The characterization of nanostructured catalyst showed that the new nanostructured catalyst has a plate‐like shape, an average particle size of 23–27 nm and superparamagnetic behavior. The nanostructured catalyst can also be recycled at least eight times without a significant decrease in catalytic activity.